2014
DOI: 10.1038/srep05963
|View full text |Cite
|
Sign up to set email alerts
|

A programmable closed-loop recording and stimulating wireless system for behaving small laboratory animals

Abstract: A portable 16-channels microcontroller-based wireless system for a bi-directional interaction with the central nervous system is presented in this work. The device is designed to be used with freely behaving small laboratory animals and allows recording of spontaneous and evoked neural activity wirelessly transmitted and stored on a personal computer. Biphasic current stimuli with programmable duration, frequency and amplitude may be triggered in real-time on the basis of the recorded neural activity as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…This structure makes easier and more reliable both the implementation of the single module and its integration in the complete system. Parallel development of components could also accelerate the ultimate realization of a device compact and powerful enough to be used as clinical tool able to transfer data between the brain and external devices wirelessly through an implanted interface (Azin et al, 2011; Fan et al, 2011; Borton et al, 2013; Angotzi et al, 2014). In this work, we also demonstrated that the modular architecture does not affect BMI performances, showing results comparable with the ones achieved in Vato et al (2012); this result suggests that BMI systems developed in other labs could also be re-implemented in a modular manner.…”
Section: Discussionmentioning
confidence: 99%
“…This structure makes easier and more reliable both the implementation of the single module and its integration in the complete system. Parallel development of components could also accelerate the ultimate realization of a device compact and powerful enough to be used as clinical tool able to transfer data between the brain and external devices wirelessly through an implanted interface (Azin et al, 2011; Fan et al, 2011; Borton et al, 2013; Angotzi et al, 2014). In this work, we also demonstrated that the modular architecture does not affect BMI performances, showing results comparable with the ones achieved in Vato et al (2012); this result suggests that BMI systems developed in other labs could also be re-implemented in a modular manner.…”
Section: Discussionmentioning
confidence: 99%
“…134 Alessandro Vato et al demonstrated bidirectional BMI in rodents; early validation showed it capable of stimulating the brain upon detection of some target activity. 159 Vato et al also demonstrated a bidirectional BMI algorithm that maps the state of an external device (e.g., position) into a series of electrical impulses while transforming recordings from the motor cortex into a tunable output force. Such a paradigm could conceivably be applied toward the operation of an artificial limb.…”
Section: Current Interfaces In the Cnsmentioning
confidence: 99%
“…PennBMBI also provided two channels of stimulation with a stimulation compliance voltage of ±12 V. In addition to neural signal recording and stimulation, inertial, temperature and force measurements can be reported via a body sensor network. In [12], a 16-channel (eight channels for recording and eight channels for stimulation) wireless portable system with both recording and stimulation capabilities was presented. More recently, a wireless headstage with 32-channel neural signal recording and up to 32-channel optical stimulation has been presented in [13].…”
Section: Introductionmentioning
confidence: 99%
“…While the electrode arrays and sense electronics are implanted, almost all computational functions are performed by external components. Further, according to [12], one must find a balance among the limited resources due to the small form factor. The studies mentioned in the above literature either lack the ability to integrate all functional components into a reasonably small-sized enclosure or have a satisfactory size, but not fully-bidirectional communication.…”
Section: Introductionmentioning
confidence: 99%